Metic Awards: Nexus approach towards globally marketable engagements - UiTM, Faculty of Business and Management (UiTM, 2023)
FBM members receiving four Metic Awards for 12/2023 presented by the Vice Chancellor of UiTM, Professor Datuk Ts. Dr. Hajah Roziah Mohd Janor, and the Deputy Vice Chancellor (Industry, Community and Alumni Network), Professor Mohamad Hariri Abdullah.